Quantifying and Reducing Retained Botulinum Toxin Postinjection. Issue 1 (31st January 2019) - Solinsky, Ryan; Kirshblum, Steven C.
Abstract : Background: Retained botulinum toxin solution may be visible in vials and syringe tips after mixing and presumed complete injections, leaving patients without the full prescribed dose. Objective: To quantify the mean amount of retained toxin within vials, syringes, and needles following spasticity injections (phase 1) and to design/test a targeted intervention for reduced retained toxin (phase 2). Design: Prospective cohort quality assurance study. Setting: Outpatient spasticity program in a rehabilitation facility. Participants: Nine physicians specializing in physical medicine and rehabilitation, performing successive mixing and injections for spasticity with onabotulinumtoxinA or incobotulinumtoxinA. Methods: After initial review (phase 1), recommendations were made (phase 2) including not inverting the vial to withdraw medication unless needed, favoring 2‐mL dilutions when possible, and decapping of vials for more complete medication withdrawal. Main Outcome Measurements: Retained volume of toxin solution that was not injected and estimated retained units of toxin. Results: A total of 157 vials of botulinum toxin A were tested. Of the 82 initial, phase 1, preintervention vials (8200 units), 5.5% (∼452 units) of toxin solution was retained following mixing and injections. One and 3‐mL syringe tips contained a mean of 3.32 and 1.44 units of toxin respectively. Within vials, saline dilutions with 2 mL contained less mean retained toxin (1.89 vs 3.31 units) relative to 1‐mL dilution. Awareness of monitoring significantly decreased retained solution in vials (0.035 mL vs 0.069 mL for naïve group, P  = .002). Phase 2, postintervention testing of 75 vials demonstrated that withdrawing toxin from the inferior edge from a non‐inverted vial reduced the retained toxin by 32.8% ( P  < .001). Decapping the vial further reduced the mean retained toxin to 0.42 units per vial (81.9% reduction, P  < .001). Conclusions: A potentially clinically significant amount of botulinum toxin solution is retained following mixing and injections. Implementation of guidelines significantly decreased wasted botulinum toxin. Level of Evidence: III